2012
DOI: 10.1097/ta.0b013e3182245ece
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-behavioral determinants of pain and disability two years after traumatic injury

Abstract: Results suggest that fear of movement and catastrophizing are risk factors for poor long-term outcomes after traumatic injury. Prospective studies are warranted to test the fear-avoidance model and determine whether the model may be relevant for explaining the development of chronic pain and disability in trauma survivors. The identification of subgroups based on negative pain beliefs may have the potential to improve outcomes after traumatic injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…However, even when controlling for some of these related factors, catastrophizing often retains significant unique, predictive influence (though it is true that no published studies, to our knowledge, control for every other variable listed here). For example, after statistically adjusting for indices of depression and anxiety, catastrophizing remained significantly associated with such diverse outcomes as return to work 77;217 , pain-related physical disability 94 , risk for prescription opioid misuse 155;156 , brain responses to a noxious stimulus 79;144 , pain intensity 8 , pain tolerance 226 , and suicidal ideation 62 . Moreover, catastrophizing likely interacts with other processes such as social support 26 .…”
Section: Psychosocial Factors Influencing Pain-related Outcomesmentioning
confidence: 99%
“…However, even when controlling for some of these related factors, catastrophizing often retains significant unique, predictive influence (though it is true that no published studies, to our knowledge, control for every other variable listed here). For example, after statistically adjusting for indices of depression and anxiety, catastrophizing remained significantly associated with such diverse outcomes as return to work 77;217 , pain-related physical disability 94 , risk for prescription opioid misuse 155;156 , brain responses to a noxious stimulus 79;144 , pain intensity 8 , pain tolerance 226 , and suicidal ideation 62 . Moreover, catastrophizing likely interacts with other processes such as social support 26 .…”
Section: Psychosocial Factors Influencing Pain-related Outcomesmentioning
confidence: 99%
“…There has been increasing evidence to support the importance of pain‐related psychosocial factors, such as low pain self‐efficacy, pain catastrophizing, and fear of movement, to poor pain and disability outcomes after traumatic orthopedic injury (Archer, Castillo, Wegener, Abraham, & Obremskey, ; Archer, Devin, et al, ; Castillo et al, ; Castillo, Wegener, Heins, et al, ; McCarthy et al, ; Nota, Bot, Ring, & Kloen, ). The Lower Extremity Assessment Project study first reported on the importance of low self‐efficacy (the patient's confidence in being able to resume life activities) to long‐term outcomes following traumatic lower‐extremity injury (Bosse et al, ), with more recent evidence supporting the association between self‐efficacy and pain at hospital discharge (Archer, Abraham, Song, & Obremskey, ). Archer et al and others have also found that patients who display pain catastrophizing behavior (tendency to focus on, ruminate, and magnify pain sensations) and/or fear of movement are at risk for more severe pain and disability up to 2 years after trauma (Archer, Abraham, & Obremskey, ; Archer, Abraham, et al, ; Nota et al, ; Vranceanu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The Lower Extremity Assessment Project study first reported on the importance of low self‐efficacy (the patient's confidence in being able to resume life activities) to long‐term outcomes following traumatic lower‐extremity injury (Bosse et al, ), with more recent evidence supporting the association between self‐efficacy and pain at hospital discharge (Archer, Abraham, Song, & Obremskey, ). Archer et al and others have also found that patients who display pain catastrophizing behavior (tendency to focus on, ruminate, and magnify pain sensations) and/or fear of movement are at risk for more severe pain and disability up to 2 years after trauma (Archer, Abraham, & Obremskey, ; Archer, Abraham, et al, ; Nota et al, ; Vranceanu et al, ). Overall, studies suggest that psychosocial risk factors, especially those related to pain beliefs and behaviors, are potential targets for cognitive and behavioral strategies that address maladaptive beliefs and avoidance of activities (Vranceanu et al, ; Zale, Ring, & Vranceanu, ).…”
Section: Introductionmentioning
confidence: 99%
“…In patients who have experienced orthopaedic trauma, little is known about these specific psychosocial risk factors. Archer et al [2] demonstrated that pain catastrophizing was associated with pain intensity, pain interference, and physical health 2 years after traumatic injury. Three studies have found that patients who display catastrophizing behavior are at risk for more severe pain and disability up to 12 months after trauma [19,42,60].…”
Section: Introductionmentioning
confidence: 99%